Efisiensi Sistem Pengangkutan Kargo Umum di Indonesia dalam Mendukung Konektivitas Maritim Nasional - Waode Rini; Eliyanti A. Mokodompit (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
This study aims to examine the existing literature related to the efficiency of general cargo transportation systems as a critical element in strengthening national maritime connectivity. Through this approach, a more comprehensive understanding is expected regarding the contributions, constraints, and factors influencing the effectiveness of general cargo transportation in supporting the smooth distribution of maritime logistics across regions in Indonesia. This research adopts a qualitative descriptive approach through a literature review. The focus of the analysis is directed toward achieving a comprehensive understanding of the efficiency of general cargo transportation in supporting national maritime connectivity. The reviewed literature is categorized based on several key aspects affecting efficiency, including infrastructure, operational processes, policy, and technology. The findings indicate that the high volume of domestic sea freight, reaching hundreds of millions of tons, demonstrates that maritime transport remains the most dominant mode for large-scale general cargo logistics in Indonesia. The growth in sea freight further reflects an increasing dependence on maritime transportation as the primary mode of inter-island goods distribution. Enhancing national maritime effectiveness can be achieved through several key indicators, including the efficiency of customs services, competitive pricing structures, the provision of high-quality logistics services, increased port infrastructure capacity, service diversification, and accelerated service completion times.